On the shoulders of giants: Molecular Biology in Public Health (Italian Journal of Public Health, 2005)
We accepted with great pleasure the invitation by professor Walter Ricciardi,our friend and colleague, to write an editorial in order to introduce this special issue dedicated to Molecular Biology in Hygiene. We are delighted for two connected reasons.First, Carmine,as a former professor of Hygiene,has passed his concepts of Hygiene on to his family and, despite significant difficulties, keeps working on the problems of preventive medicine in the work environment and in geriatrics. Second, Gerry, raised in an environment of hygienists, has dedicated all his professional efforts to Molecular Biology. As these two distinct experiences have constantly mixed within our family over time, we appreciate the promiscuous intermingling of these two disciplines in this thematic issue.The result is a useful common effort aiming at understanding the problems of diseases in the work environment and in the human environment in general.These problems have a profound social meaning, for which it is necessary to create an essential collaboration with scientific research.This is the only way to benefit human society.